IMPORTANCY OF INTERNET - Ahmedov, Azimjon Ilhomovich; Rasulova, Durdonabonu Rayimjon qizi (Educational Research in Universal Sciences, 2023)
This article provides information about the history of the origin of the Internet, views about it, Advantages and disadvantages, benefits and harms.